GLUT1 exacerbates trophoblast ferroptosis by modulating AMPK/ACC mediated lipid metabolism and promotes gestational diabetes mellitus associated fetal growth restriction - Qin Zhang; Xi Yuan; Xiaojin Luan; Ting Lei; Yiran Li; Wei Chu; Qi Yao; Philip N. Baker; Hongbo Qi; Hui Li (Molecular Medicine)
Abstract Background Gestational diabetes mellitus (GDM) has been associated with several fetal complications, such as macrosomia and fetal growth restriction (FGR). Infants from GDM associated FGR are at increased risk for adult-onset obesity and associated metabolic disorders. However, the underlying mechanisms of GDM associated FGR remain to be explored. Methods We analyzed placentas from GDM patients with FGR for ferroptosis markers and GLUT1 expression. High glucose conditions were established by adding different concentrations of D-Glucose to the 1640 cell culture medium. RSL3 were used to test ferroptosis sensitivity in trophoblast cells. GLUT1 was inhibited using siRNA or its inhibitor WZB117 to assess its impact on ferroptosis inhibition in HTR8/SVneo cell line. Mechanistic studies explored the effects of GLUT1 on AMPK and ACC phosphorylation, which in turn impacted lipid metabolism and ferroptosis. In mouse models, streptozotocin (STZ)-induced GDM was treated with WZB117 and the ferroptosis inhibitor liproxstatin-1 (Lip-1). Finally, AMPK and ACC phosphorylation levels were evaluated in GDM patient samples. Results In this study, placentas from GDM patients with FGR showed signs of ferroptosis and upregulation of GLUT1. In cell models, high glucose conditions sensitized trophoblast cells to ferroptosis and induced GLUT1 expression. Interestingly, GLUT1 inhibition significantly suppressed ferroptosis in trophoblast cells under high glucose conditions. Mechanistically, elevated GLUT1 inhibited AMPK phosphorylation and reduced ACC phosphorylation, thereby promoting lipid synthesis and facilitating ferroptosis. In pregnant mice, STZ-induced hyperglycemia led to FGR, and treatment with either the GLUT1 inhibitor WZB117 or the ferroptosis inhibitor Lip-1 alleviated the FGR phenotype. Moreover, in vivo elevation of GLUT1 increased ferroptosis markers, decreased AMPK/ACC phosphorylation, and resulted in altered lipid metabolism, which likely contributed to the observed phenotype. Finally, placental samples from GDM patients showed reduced AMPK and ACC phosphorylation. Conclusions Our findings suggest a potential role of ferroptosis in GDM associated FGR and indicate that the dysregulated GLUT1-AMPK-ACC axis may be involved in the pathogenesis of GDM associated FGR in clinicals.